Constructing "Soft‐Stiff" Structure on the Surface of Carbon Fiber to Enhance the Interfacial Properties of Its Epoxy Composites. Issue 25 (10th August 2022) - Ma, Xiaoyue; Guo, Jiaming; Wen, Shubao; Liu, Yu; Wang, Junming; Zhao, Lianshuang; Ao, Yuhui; Liu, Liu; Yan, Fei
Abstract: A "soft‐stiff" structure is equipped onto carbon fiber (CF) surface by hydrothermal and self‐assembly methods, in which MnO2 nanosheets and natural polysaccharide chitosan (CS) act as "stiff" phase and "soft" phase, respectively, leading to strong interfacial phase in CF/epoxy composite. The roughness, polar functional group content, and wettability of the CF surface are significantly promoted by this protocol. Moreover, the unique structure also serves as a buffer area to relieve stress concentration and change the direction of crack propagation, thus enhancing the interfacial properties of the composites. The strengthening effect of the "soft‐stiff" structure is verified by interlaminar shear strength (ILSS) and flexural strength tests, which are improved by 47.4% and 48.2%, respectively compared with pristine CF/epoxy composites. This work provides a potential reinforcement strategy to access high‐performance CF composites. Abstract : The interfacial interaction between fiber and resin is enhanced by constructing a "soft‐stiff" structure on carbon fiber (CF) surface. The interlaminar shear strength and flexural strength of the modified composites are 66.2 and 914.1 MPa, respectively, which are 47.4% and 48.2% higher than pristine CF/epoxy composites. This work provides a potential reinforcement strategy to access high‐performance carbon fiber composites.